Optimization of transesterification parameters for optimal biodiesel yield from crude jatropha oil using a newly synthesized seashell catalyst - Reddy, Anr; Saleh, A.A.; Md Saiful, Islam; Sinin, Hamdan (Taylor's University, 2017)
Heterogeneous catalysts are promising catalysts for optimal biodiesel yield from transesterification of vegetable oils. In this work calcium oxide (CaO) heterogeneous catalyst was synthesized from Polymedosa erosa seashell. Calcination was carried out at 900ºC for 2h and characterized using Fourier transform infrared spectroscopy. Catalytic efficiency of CaO was testified in transesterification of crude Jatropha oil (CJO). A response surface methodology (RSM) based on five-level-two-factor central composite design (CCD) was employed to optimize two critical transesterification parameters catalyst concentration to pretreated CJO (0.01-0.03 w/w %) and the reaction time (90 min - 150 min). A JB yield of 96.48% was estimated at 0.023 w/w% catalyst and 125.76 min reaction using response optimizer. The legitimacy of the predicted model was verified through the experiments. The validation experiments conformed a yield of JB 96.4%±0.01% as optimal at 0.023 w/w% catalyst to pretreated oil ratio and 126 min reaction time.